CT Test: A Powerful Tool for Assessing Computational Thinking Skills in Biology - Ryan Ardiansyah; Dea Diella; Herni Yuniarti Suhendi; Novi Febrianti (Pedagogia: Jurnal Ilmiah Pendidikan, 2024)
This research aims to create a tool for assessing students' computational thinking (CT) skills in relation to biology concepts. The study followed a research and development approach, utilizing a modified 4D design model, with the dissemination phase excluded. Various data collection techniques were employed, including observations, literature reviews, documentation, surveys, interviews, and tests. The findings showed that the developed instrument was valid, having been evaluated by three experts. The material expert rated it at 95%, the assessment and evaluation expert at 88%, and the linguist at 90%. In terms of readability, the instrument scored 75%, indicating a "good" rating. The overall validity of the instrument was found to be 0.70, placing it in the high validity range, while its reliability score was 0.82, reflecting a very high level of dependability. The assessment of students' computational thinking skills in biology revealed that 25% of students scored in the low range, 28% in the medium range, and 57% in the high range. From these findings, it can be concluded that the CT test tool is both valid and appropriate for evaluating students' computational thinking skills.